The Effect of Discipline and Work Environment on Teacher Performance at SMK Negeri 2 Pondok Aren-South Tangerang - Dayat Hidayat (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Teachers are the main key to improving the quality of education because an important requirement for the realization of quality education is if its implementation is carried out by professionally reliable educators. This study aims to determine the effect of discipline and work environment on teacher performance at SMK Negeri 2 Pondok Aren-South Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study, the discipline has a significant effect on teacher performance by 44.7%, the hypothesis test is obtained t count> t table or (7,024> 2,000). The work environment has a significant effect on teacher performance by 40.2%, hypothesis testing is obtained t count> t table or (6.398> 2,000). Discipline and work environment simultaneously have a significant effect on teacher performance with the regression equation Y = 10.637 + 0.386X1 + 0.365X2. The contribution of the effect was 54.7%, the hypothesis test obtained F count> F table or (36.188> 2.760).